The The Manhaji Method: An Innovative Approach to Enhancing Arabic Language Learning Through Qur’anic Integration - Kusuma Ningsih, Windi; Napisah, Radiatul; Al Warits , Ilman; Irfani Sahuda , Muhammad (Institut Agama Islam Negeri Palangka Raya, 2025)
Despite the proliferation of Arabic teaching methods, many traditional approaches such as the Grammar-Translation and Granada methods often isolate grammar instruction or postpone engagement with authentic texts, limiting learners’ contextual understanding. Addressing this gap, the present study examines the Manhaji Method an integrative approach that begins with Qur’anic verses and enables learners to inductively extract grammatical (naḥw) and morphological (sarf) rules. The study aims to analyze the implementation, pedagogical benefits, and challenges of this method in Arabic language education. Employing a descriptive-analytical library research design, relevant literature and teaching practices were reviewed to assess the method’s impact. Findings indicate that the Manhaji Method significantly enhances comprehension of Qur’anic vocabulary, fosters learner autonomy, and bridges theoretical knowledge with practical application. Nevertheless, its highly structured nature can pose difficulties for novice learners, necessitating adaptive instructional strategies. These insights suggest that while the Manhaji Method offers a holistic and scalable framework for improving both Arabic proficiency and Qur’anic literacy, its application should consider learner readiness and instructional flexibility. This study contributes to the discourse on innovative Arabic pedagogy and underscores the potential of integrating religious texts meaningfully into language instruction.